The influence of ownership structure on the development of international activities of international business entities - Sunigovets, O. M. (Baltija Publishing, Riga, Latvia, 2020)
The purpose of the article is to generalize the existing views on ensuring the effectiveness of international business entities in the context of globalization trends and the implementation of the tasks of domestic companies to enter international markets. Systematization of problems of international business development on the basis of the research of the impact of structural aspects in ensuring economic development, with special emphasis on studying the development of the ownership structure of international business in the formation of the foundations of sustainable economic growth. Methodology. The study is based on comparing trends in the development of international business of countries, processing the results of studying the issues of the topic by domestic and foreign economists, domestic and foreign literature, statistical data, the results of analytical studies of rating agencies, international organizations. In the process of research, the method of theoretical generalization and comparison, and general scientific research methods were used, mainly, analysis, synthesis, abstraction. The information basis of the research consisted of the works of domestic and foreign scientists on the problems of the theory of international business, international economic relations, international management, and international corporate governance of international business. The results of the research showed that the modern conditions for conducting international business were changing dynamically, which required the development of international business entities special improvement of existing approaches to management in accordance with the conditions of globalization, manifestation of innovative development and striving for openness as the best way of modern coexistence. The country’s position in the world economic system is determined by the structure of the economy. Practical implications. Thus, the structure of the economy determines the possibilities of economic development, the ownership structure is an important aspect in ensuring the efficiency of international business. In the context of globalization, corporate governance is seen as a tool for development and needs improvement for the enterprises to enter into international markets. The ownership structure is able to determine the innovative potential of enterprises in world markets. Value/originality. The identified current trends in the development of structural relationships of the economy based on the generalization of research on structural interdependencies in creating the preconditions for sustainable economic development allows to determine the basis for the actions of international business in the globalization and manifestations of innovative economy more objectively. The special value of the work lies in a more detailed study of the ownership structure in ensuring the efficiency of international business and the effects of globalization, which determines the main directions of improving Ukrainian enterprises, their organizational and legal forms of doing business to ensure compliance with international business principles and access to international markets.
Keywords: globalization and innovation development; economic structure; ownership structure; international business; business efficiency; corporate governance